History of Polish and German Village Councils in the Ukrainian SSR during the Period of “Korenization” through the Prism of New Historical Sources - Sinkevych, Yevhen (Ukrainian Peasant, 2025)
The purpose of this article is a comprehensive analysis of archival sources concerning the activities of Polish and German village councils in the Ukrainian SSR during the period of korenizatsiya. The scientific novelty of this publication lies in the integrated approach to studying archival materials related to the activities of Polish and German councils in the Ukrainian SSR during the korenizatsiya policy. The collapse of the Russian Empire after World War I prompted subjugated nations to seek independence. Ultimately, the Ukrainian liberation struggle ended in failure, and Ukraine was left with a quasi-state within the USSR. The Kremlin authorities were forced to reckon with the aspirations of various peoples to develop their own language and culture, which led to the implementation of the so-called korenizatsiya policy. Village councils became the focal points of this policy. While the Ukrainian dimension of korenizatsiya (i.e., Ukrainianization) has been widely covered in recent decades, the application of korenizatsiya among Polish and German village councils remains insufficiently explored. This study involves analysis of printed sources and archival searches in central archives (Kyiv) as well as in the state archives of Mykolaiv, Kherson, and Khmelnytsky regions. Conclusions. Analysis of published and archival sources indicates that the Soviet policy of korenizatsiya, actively implemented through Polish and German village councils in the Ukrainian SSR, was intended to win over national minorities. However, it was a temporary measure: as administrative control and punitive structures strengthened, korenizatsiya was dismantled, and Poles and Germans were subjected to repression.